Determinan kemiskinan di Provinsi Jambi - Ronald Banito, Fran; R, Rachmad.; Zulfanetti, Zulfanetti (Jurnal Paradigma Ekonomika, 2022)
Poverty is a global social problem, meaning that poverty is a problem that must be faced and a concern of many people. This study aims to analyze the development of poverty and the determinants of poverty in Jambi Province. This study uses a secondary data analysis method, and the data used is data from the Central Statistics Agency of Jambi Province. And the data used is the times series 2002-2019. This study uses multiple regression analysis with the level of poverty as the dependent variable, inflation, GRDP, Average Years of Schooling (RLS), Labor Force Participation Rate (TPAK), and Provincial Minimum Wage (UMP) as independent variables, and uses a dummy variable 1 Jambi Provincial government policies related to poverty reduction through the Jamkesda Program. The results of this study indicate that the development of the poverty rate in Jambi Province for the 2002-2019 period tends to decrease and that inflation, GRDP, RLS, UMP, and Dummy 1 (Jamkesda) have an effect significantly on the poverty rate in Jambi Province in the period 2002-2019.